Electronic and magnetic properties of germanene: Surface functionalization and strain effects. (January 2016) - Liang, Pei; Liu, Yang; Xing, Song; Shu, Haibo; Tai, Bo
Abstract: The surface functionalization and strain effects on the structural, electronic, and magnetic properties of full-/half-passivated germanenes are investigated systematically by the first-principle calculations within density functional theory. It is found that the germanenes with full-passivation have different band structures. i.e., the band-gap of GeH is larger than that of GeF and GeCl. Interestingly, when surface passivation and strain are utilized, germanenes go through a transformation from semiconductor to semi-metal. Moreover, germanenes with half-passivation present different magnetic characters, i.e, . Ge2 H is a ferromagnetic semiconductor, while Ge2 F and Ge2 Cl are anti-ferromagnetic semiconductors. The stability of magnetic coupling of Ge2 Xs can be modulated by external strain. Our calculations indicate that the electronic and magnetic properties of passivated-germanenes strongly depend on their surface functionalization and strain effects. Highlights: The germanenes with full-passivation have different band structures. i.e., the band-gap of GeH is larger than that of GeF and GeCl. When surface passivation and strain are utilized, germanenes go through a transformation from semiconductor to semi-metal. The stability of magnetic coupling of Ge2Xs can be modulated by external strain.